Predation of Eurolophosaurus aff. divaricatus (Sauria: Tropiduridae) by Philodryas nattereri (Serpentes: Colubridae) - Gonçalves Sousa, José Guilherme; Cardozo Ribeiro, Samuel; Oliveira, Júlia S.; C. de Kokubum, Marcelo N.; Mesquita, Daniel O.; Colli, Guarino R.; Guedes, Thaís B. (Herpetologia Brasileira, 2026)
This study reports the first record of predation on the lizard Eurolophosaurus aff. divaricatus, with the snake Philodryas nattereri as the predator. The event was observed on October 23, 2023, in the paleodunes of the São Francisco River, in Casa Nova municipality, Bahia, Brazil. We found an adult P. nattereri swallowing an adult E. aff. divaricatus inside a pitfall trap. As we approached, the snake quickly regurgitated its prey and escaped from the trap. Although E. aff. divaricatus has a restricted distribution, its local populations are relatively dense. Consequently, it is not surprising that P. nattereri preys on this lizard, given the relative abundance of E. aff. divaricatus and the generalist feeding habits and wide geographic distribution of this snake. This record highlights the incidental predation that can occur in pitfall traps and emphasizes the importance of frequent trap monitoring to minimize such events, particularly in areas of high endemism.